Effectiveness of Using Interactive Media Based on Lectora Inspire to Improving the Quality of Chemistry Science Learning in Second Grade at Junior High School/Madrasah Tsanawiyah - Herdini, Herdini; Linda, Roza; Abdullah, Abdullah; Ramadhan, Ahmad Khairu (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research is implementation of the results of development research in previous year. The aim is to investigate the effectiveness (impact) of using the valid and practical interactive media based on Lectora Inspireto the quality of Chemistry Science Learning in Junior High Schools/Madrasah Tsanawiyah (especially studentsâs activities and learning outcomes). The research is an experiment with randomized control group pretest-posttest design. To know the studentsâs learning outcomes by using right-hand t-test and to know their learning activities by using observation sheet. The samples were determined randomly after normality and homogeneity test. VIII-A-3 was experiment class and VIII-A-4 was control class in this research at MTs Dar El Hikmah Pekanbaru. The experimental class was treated by using of Lectora Inspiremedia while the control class was not. Based on data analysisâs results, obtained tct = 8,14 and ttable = 1,67 with Î± = 0,05, dk = 72. tct> ttable which is 8,14 > 1,67 means the using of Lectora Inspiremedia can improved the studentsâs learning outcomes. Beside that, the studentsâs learning activities in experimental class is in a very good range while in control class is in a good range.